HUBUNGAN USIA DENGAN PEMILIHAN JENIS KONTRASEPSI SUNTIK DI BPS NY.NANIK SUWATI, S.ST KELURAHAN KAUMAN KECAMATAN MOJOSARI KABUPATEN MOJOKERTO - Dyah Siwi Hety (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2014)
Prevention of mother’s fatality and morbidity is the main reason for needed of family planning services. Many women, have difficulties in determining the type of contraception. To deciding which method will be used, influenced by personal factor one of them is age. From the data obtained. The most people usage of contraceptives is injection. The purpose from this research is to know the connection between age and selection of contraceptive in BPS Mrs. Nanik Suwati, S.ST Kauman Mojosari. This research is using cross sectional planning method with population of acceptors KB injection in BPS Mrs.Nanik Suwati,S.ST Kauman Mojosari in January-April 2014 amount 168 people. A lot of sample was obtained from acceptors KB injection in BPS Mrs. Nanik Suwati, S.ST Kauman Mojosari in the January- April 2014 amount 168 people. This research have been made in 20 May-20 June 2014 on the location of research in BPS Mrs. Nanik Suwati,S.ST Kauman Mojosari which take with non probability sampling technique total sampling, the data collection was using a checklist of secondary data and the data analyzed was using with uji Chi-Kuadrat. From the research result were obtained at most 20 – 30 years of age who choose to inject as many as 66 people a month (39,3 %). The data analyzed by using uji Chi Kuadrat, concluded so there is a relationship between age with the choice of contraceptive injection in BPS Mrs. Nanik Suwati,S.ST Kauman Mojosari. According with the research result be provided to improve the quality of service about choosing the contraceptive which accordance with the age.